IDENTIFIKASI INDEKS KENYAMANAN KOTA YOGYAKARTA BERDASARKAN KRITERIA CULTURAL HERITAGE - Ayu Candra Kurniati; Fahril Fanani (TATALOKA, 2019)
The ideal city planning, in fact is the combination between livable and sustainable city, where the city is able to maintain the quality of life in the present as well as the future, furthermore it generates a comfortable atmosphere for a place to live as seen from many aspects.  Yogyakarta is one of the livable cities in Indonesia with the highest index score, 68.14% for social life and 70.89% for the preservation of cultural heritage building. Considering the mission of Yogyakarta which is to enhance cultural quality and strengthen morality, behavior and cultural value of the community, it is considerable to conduct a research regarding to livable city index in Yogyakarta based on the criteria of cultural heritage.   Furthermore, this research used scoring dichotomy data as a methodology with variables: the changes in building's form and function, the ownership status and the usage of cultural heritage building, as well as the amount of cultural heritage buildings that have been demolished and/or in the process of demolition. The results show the highest livable index for preservation of cultural heritage building is in cultural preservation area Kotagede (41.77%), followed by Kraton (20.66%), Malioboro (14.06%), Pakualaman (13.21%) and the least is Kotabaru (10.03%). Kotagede has the highest livable index due to the amount of cultural heritage building compared to other preservation areas. From the total percentage, 42.9% of the buildings are in the original form, 30% have its function changed, 70% are in personal ownership, 21.6% are in group/association, and 45.5% are not demolished. The conclusion of this study is that the existence of cultural heritage building in the city will increase the value of environmental identity which is resembles the character of the area and the community within